Analisis Kemampuan Literasi Statistika Mahasiswa Pendidikan Sosiologi - Syarief, Nur Hasanah; Aba, Maria Martini; Zulfikar, Ryan Nizar (Edumatica : Jurnal Pendidikan Matematika, 2023)
This research aims to identify students' statistical literacy abilities, and this type of research is descriptive qualitative. The subjects in this research consisted of 24 Sociology Education students from Muhammadiyah University of Kupang taking statistics courses in the 2023/2024 academic year. The instrument used is an assignment consisting of 2 questions. Data analysis was done by analyzing students' answer documents to complete the assignments given. Students' statistical literacy abilities are identified using five statistical literacy competencies: understanding statistical concepts, insight into the application of statistical concepts, calculation and graphing skills, interpretation abilities, and visualization and communication skills. The research results show that more than 50% of students can fulfill statistical literacy competencies such as understanding statistical concepts, numeracy, interpretation, and communication skills. However, less than 50% of students do not meet competency in insight into the application of statistical concepts and visualization skills. Students' abilities in essential statistical literacy competencies still need to be improved because most students still have limitations in these competencies.